A Novel Approach to Preparing Highly Porous and Dispersed Supported Nickel Catalyst. Issue 35 (13th December 2017) - Cui, Sha; Wang, Zhenqing; Wang, Genggeng; Yang, Ying; Liu, Baijun
Abstract: This article proposes a new synthesis of amorphous silica‐alumina (ASA) supported Ni catalyst using hydrothermal synthesis method by the assistant of cis‐9‐octadecenylamine. Cis‐9‐octadecenylamine, as a coordination agent and surfactant, could form Ni‐cis‐9‐octadecenylamine complex with nickel salt under hydrothermal condition, which boosts the metal dispersion. Characterization results by N2 adsorption‐desorption shows that the as‐prepared catalyst is provided with enhanced porosity, especially mesoporous and by XRD, TEM and H2 ‐TPR display that the resulting Ni particles are very small and uniform. The ASA supported Ni catalyst proves to be highly efficient and stable in naphthalene hydrogenation, and gives 100% conversion and more than 99% selectivity to decalin with an extremely wide activity window at 180∼280 °C, which is superior to its counterparts prepared via traditional impregnation method. Abstract : This article proposes a new synthesis of amorphous silica‐alumina (ASA) supported Ni catalyst using hydrothermal synthesis method by the assistant of cis‐9‐octadecenylamine. The as‐prepared catalyst is provided with enhanced porosity and improved Ni particles dispersion, and proves to be highly efficient and stable in naphthalene hydrogenation.